2014
DOI: 10.1007/s11079-013-9301-9
|View full text |Cite
|
Sign up to set email alerts
|

Banking and the Macroeconomy in China: A Banking Crisis Deferred?

Abstract: The downturn in the world economy following the global banking crisis has left the Chinese economy relatively unscathed. This paper develops a model of the Chinese economy using a DSGE framework with a banking sector to shed light on this episode. It differs from other applications in the use of indirect inference procedure to test the fitted model. The model finds that the main shocks hitting China in the crisis were international and that domestic banking shocks were unimportant. However, directed bank lendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
6
22
0
Order By: Relevance
“…The second column gives the results which show that models can be found that are not rejected for key sets of macro variables such as output, in ‡ation and interest rates. The …ndings of Le et al (2010Le et al ( , 2011Le et al ( , 2014 are that, in general, models which can match a VAR(1) on a limited number of variables, do not perform as well on VARs with many more variables, and are typically rejected for higher-order VARs than a VAR (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second column gives the results which show that models can be found that are not rejected for key sets of macro variables such as output, in ‡ation and interest rates. The …ndings of Le et al (2010Le et al ( , 2011Le et al ( , 2014 are that, in general, models which can match a VAR(1) on a limited number of variables, do not perform as well on VARs with many more variables, and are typically rejected for higher-order VARs than a VAR (1).…”
Section: Discussionmentioning
confidence: 99%
“…This work is all on US data for the period since the mid-1980s; we have not found it possible to mimic US behaviour for earlier data, we think because there has been substantial regime change before then- Le et al (2014).…”
Section: Using These Methods To Test a Modelmentioning
confidence: 98%
“…There is also a body of work modelling the Chinese economy s business cycle behaviour as a Dynamic Stochastic General Equilibrium (DSGE) model, in the manner applied to major developed economies. Le et al (2014) review these developments in the context of a model of China spanning the financial crisis. Even though China is at an earlier stage of development than these, a DSGE model does not appear to make assumptions that restrict its application to countries at earlier stages, provided these economies have normal market structures.…”
mentioning
confidence: 99%
“…Le et al (2014) build a DSGE model based on Wouters (2003, 2007), combined with the financial accelerator mechanism of Bernanke et al (1999). They argue that as a result of government intervention, China was relatively unscathed during the world crisis.…”
Section: Financial Friction and Banking Dsge Modelsmentioning
confidence: 99%
“…Existing literature cannot clearly explain the mechanism whereby the banking sector amplifies the shocks, and to date no study has incorporated the two different kinds of firms into the model. As mentioned in Le et al (2014), intervention by government forced the state-owned banks to financially support state-owned firms during the period of global financial crisis, leading to a Chinese credit boom in the following period and causing surplus productivity in manufacturing, stimulating the deferred bank crisis to explode.…”
Section: Financial Friction and Banking Dsge Modelsmentioning
confidence: 99%